TiB2 ceramic and DLC Multilayered PVD coatings - Santos da Silva Cruz, Ricardo Manuel (Cranfield University, 2007)
Titanium diboride (TiB2) has been investigated as a potential candidate for several industrial applications, such as: cutting tools, electric devices, wear parts and many more fields of application. The main drawback of TiB2 is its brittle nature, which has limited its range of applications. Diamond-like Carbon (DLC) has been used in industrial applications, mainly for wear resistant parts. However, the application of DLC films has been limited by the level of internal stress accumulated during deposition. This thesis investigates the deposition of TiB2/DLC multilayer wear resistant coatings to overcome these limitations. The thesis focuses on the tribological effects caused by different deposition techniques on TiB2 ceramic used by the coatings industry today, in order to overcome the brittle nature of TiB2 and the lack of adhesion of DLC films. The multilayer coatings consisted of 25 bi-layers of TiB2/DLC. These TiB2/DLC coatings were fabricated, maintaining a constant composition wavelength (sum of two layers Î» =200 nm) for an array of ceramic fractions ranging from 25% to 95% by volume using as substrates, tool steel AISI 1095 and powder metallurgy aluminium alloys, type 2618. The effect of the DLC content on the structure and performance (hardness, adhesion and wear) of the films was investigated. The bi-layer thickness influences the failure patterns observed in the scratch testing. These observations have been used to optimise the multilayered coating structure. Multilayer coatings have been manufactured to increase surface hardness and wear resistance as applied to a commercial powder metallurgy Al alloys (Al 2618) used in the automotive industry. Optimum coatings have found hardness values of 27.8 GPa, with a critical load of 20 N and a friction coefficient of 0.47. As a result of wear tests the multilayer with 10% of DLC was found to be best compromise between high hardness (23.8 GPa), good adhesion (critical load higher than 20 N), low friction and low wear rate.